Glodilocks and the three bears - Mahmoud, Youmna; ESC Creative Department ([Cairo] Educational Services Company, 2024)
A young girl went for a walk in the forest. She discovered an empty house. Her curiosity made her enter that house and discover if from inside. But, is it acceptable to enter a house without permission. Is it proper to act before thinking?
English Stories
Keywords: English stories